Relationship between vitamin intake and total antioxidant capacity in elderly adults - Ojeda Arredondo, Miriam Lucia; Pontificia Universidad Javeriana, Faculty of Sciences, Department of Nutrition and Biochemistry, Grupo de Nutrición, Alimentación y Salud, Bogotá, Colombia. (2016)
The consumption of foods high in natural antioxidants, like fruits and vegetables, is associated with a lower risk of oxidative stress-related diseases. The aim of this study was to establish the relationship between the plasma antioxidant capacity in adults over fifty and their intake of vitamin A, C, and E. We evaluated 118 24-hour recalls of intake of foods. The intake of vitamin A, C, and E was quantified using food composition tables. We quantified plasma phenols using the Folin-Ciocalteu method. The antioxidant capacity was determined using the Trolox Equivalent Antioxidant Capacity (TEAC) and Oxygen Radical Absorption Capacity (ORAC) methods. Correlation analyses were performed between the studied variables and a positive correlation was found in most cases. However, none of the correlations was statistically significant. In all cases p-value was >0.05. The quantification of nutrient intake is not an adequate predictor of plasma antioxidant capacity in individuals over fifty